2012
DOI: 10.1063/1.4717241
|View full text |Cite
|
Sign up to set email alerts
|

Photonic band effect in single-layers of high refractive index spheres of different compactness

Abstract: Transmission spectra from single-layers of high dielectric permittivity (ɛ = 7) glass spheres have been measured, in microwave region, for different angular incidences. The same systems have been calculated by Finite-Difference Time-Domain (FDTD) method. The dispersion diagrams of photonic bands in triangular geometries have been obtained for a number of different compactness cases. The experimental and the calculated photonic band structures show a good agreement in all the compactness values studied. They we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 19 21 Andueza et al proposed a numerical method to investigate light scattering by particles based on the Maxwell equations. 22 Ma et al indicated that the scattering of particles has remarkable connections with the particle complex refractive index. 23 Di Biagio et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 21 Andueza et al proposed a numerical method to investigate light scattering by particles based on the Maxwell equations. 22 Ma et al indicated that the scattering of particles has remarkable connections with the particle complex refractive index. 23 Di Biagio et al.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, numerous studies related to the absorption and scattering of particles have been widely conducted. Andueza et al proposed a numerical method to investigate light scattering by particles based on the Maxwell equations . Ma et al indicated that the scattering of particles has remarkable connections with the particle complex refractive index .…”
Section: Introductionmentioning
confidence: 99%
“…The lattice geometry used was triangular, with a parameter notation: Φ for the sphere diameter and Λ to refer to the lattice constant, the separation between two consecutive centers in the unit cell. The dielectric constant of the spheres was selected to be ε = 7, similar to Soda Lime glass used in [22][23][24][25][26]. To indicate the compactness of a particular arrangement, filling factor parameter was used and denoted by f f .…”
Section: Calculation Proceduresmentioning
confidence: 99%